Preferences and skills of Indian public sector teachers - Sonja Fagernäs; Panu Pelkonen (Institute for the Study of Labor (IZA), 2012)
With a sample of 700 future public sector primary teachers in India, a Discrete Choice Experiment is used to measure job preferences, particularly regarding location. General skills are also tested. Urban origin teachers and women are more averse to remote locations than rural origin teachers and men respectively. The joint analysis of preferences and skills suggests that existing caste and gender quotas are detrimental for the objective of hiring skilled teachers willing to work in remote locations. The most preferred location is home, which supports decentralised hiring, although evidence suggests that in remote areas this could compromise skills.
urn:nbn:de:101:1-201301213258
Keywords: I25; J33; J45; 330; discrete choice experiment; teacher recruitment; job preferences; hiring quotas; skills; India; Lehrkräfte; Personalbeschaffung; Qualifikation; Präferenztheorie; Region; Diskrete Entscheidung; Test; Indien